On the optimal strut-and-tie models and design approach for the cable-pylon anchorage zone - Cui, Nannan; Huang, Shiping (Journal of Civil Engineering and Management, 2019)
The cable-pylon anchorage zone is a typical D-region in a cable-stayed bridge, for which there has been no uniform simplified design method until now. In this paper, based on the extensive statistics of actual projects, topology optimization techniques and principle of minimum strain energy, two precise strut-and-tie models for the cable-pylon anchorage zone are proposed, which can clearly reveal the load-transmitting mechanism of the anchorage zone. Th e explicit geometric parameters of the strut-and-tie models are derived; thus, the designers can directly use these models. A simple design procedure to deploy prestressing tendons in the anchorage zone is also introduced, whose effectiveness and convenience are demonstrated by two design examples. A new design named the “one-way prestressing tendons PC cable-pylon” is also discussed regarding its application scope.